Work Motivation as a Mediator of Employee Well-Being, Leadership, and Staff Performance - Ahmad Firman; Fitriani Latief; Andi Nabila Tenri Lala (Advances in Human Resource Management Research, 2026)
Purpose: This study examines the effects of employee well-being and transformational leadership on educational staff performance and investigates the mediating role of work motivation in private universities. Research Method: A quantitative explanatory approach was employed. Data were collected through questionnaires from 75 educational staff members at private universities specializing in economics in South Sulawesi, Indonesia. Respondents were selected using purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Results and Discussion: The results show that employee well-being and transformational leadership positively and significantly influence work motivation. Transformational leadership and work motivation significantly affect educational staff performance, whereas employee well-being has no direct effect on performance. Furthermore, work motivation significantly mediates the relationships between employee well-being and performance, as well as transformational leadership and performance. These findings indicate that motivation is a key mechanism linking leadership and employee well-being to improved performance outcomes. Implications: University management should strengthen transformational leadership practices and promote employee well-being to enhance work motivation and staff performance. Originality: This study provides evidence of the mediating role of work motivation in explaining how employee well-being and transformational leadership influence educational staff performance in Indonesian private universities.